Efecto de la propiocepción en el pase con categorías inferiores de futbol - Gómez Coca, Bryan Alexis (2025)
The research was based on the objective of evaluating the effects of proprioception in the execution of passes in U-13 players of the Club Técnico Universitario. Proprioception is considered as the ability to perceive the position and movement of body parts, which directly influences giving possession of the ball to another player. The specific objectives included: determining the relationship between proprioception and the execution of passes, to correlate the test results with the performance in game situations and to design training strategies to optimize this technical skill. The theoretical foundation was based on a study of scientific literature, books and theses on its influence on sports performance, as another relevant factor is the classification of the different types of passes in soccer and their importance in the U-13 category. The methodology used is quantitative and descriptive, with collection and analysis of data obtained from players of the Club Técnico Universitario, using a non-probabilistic random sampling. The players participated in structured proprioception sessions, the effects of which were evaluated using statistical methods. The results reflected significant advances in ball control, passing strength and precision in in-game decision making. It was confirmed that soccer, as an organized discipline, strengthens not only the technical skills, but also the cognitive and social abilities of the players. As a result, adapted plans were designed with strategies for teaching passing, focused on improving precision, speed and control. It addresses motor coordination, efficient use of space and group interconnection, promoting innovative sports training. The intervention plan seeks to enhance the performance of players through specific proprioception exercises, facilitating their technical and tactical development in the training process